2021
DOI: 10.1177/1077801220985937
|View full text |Cite
|
Sign up to set email alerts
|

Understandings and Perceptions of Domestic Violence Among Newly Arrived Afghan Women in Australia

Abstract: Women’s perceptions of domestic violence vary across societies and cultures and might change by moving to a new society. This study aims to explore newly arrived Afghan women’s understandings and perceptions of domestic violence and whether they perceive this as acceptable. Semi-structured interviews were conducted with 21 newly arrived Afghan women in Australia. Interviews were audio-recorded, transcribed, and analyzed inductively to generate and organize themes. The findings showed that informants had a soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Some of the examined articles emphasized the impact of the new environment on the refugee women's attitude toward IPDV; for example, Afrouz and colleagues reported that resettlement in a new environment impacts women's perspectives on IPDV, viewing it as abnormal and unacceptable (Afrouz et al 2021a). In another study, a change in women's attitudes was reported to depend on their education level, English proficiency, personal experience of IPDV, years of living in the host country, connecting with the host society, and pursuing education in the new home (Afrouz et al 2021b). Tlapek, S. M. and colleagues also reported that refugee women in their host countries encounter new gender roles that can increase daily relational confrontations; refugee women may stand up to their partners, ask for shared decision-making, and no longer tolerate inadequate pre-resettlement gender norms (Tlapek et al 2020).…”
Section: Thematic Analysismentioning
confidence: 98%
See 4 more Smart Citations
“…Some of the examined articles emphasized the impact of the new environment on the refugee women's attitude toward IPDV; for example, Afrouz and colleagues reported that resettlement in a new environment impacts women's perspectives on IPDV, viewing it as abnormal and unacceptable (Afrouz et al 2021a). In another study, a change in women's attitudes was reported to depend on their education level, English proficiency, personal experience of IPDV, years of living in the host country, connecting with the host society, and pursuing education in the new home (Afrouz et al 2021b). Tlapek, S. M. and colleagues also reported that refugee women in their host countries encounter new gender roles that can increase daily relational confrontations; refugee women may stand up to their partners, ask for shared decision-making, and no longer tolerate inadequate pre-resettlement gender norms (Tlapek et al 2020).…”
Section: Thematic Analysismentioning
confidence: 98%
“…Afrouz et al reported that Afghan women have different levels of understanding and define IPDV differently. Women without sound knowledge of IPDV might perceive violence as normal (Afrouz et al 2021b). Abdel Meguid, M. B. and colleagues also reported a wide range of responses on the definition of abusive words and abusive actions; as an example, women agreed that "men making fun of their wives in front of others or calling them names" are examples of emotional abuse, and most agreed that physical abuse is not acceptable; however, actions like "forced intercourse or refusing to have sex with the wife if she is not obedient" were reported as less abusive (Meguid and Bakry 2006).…”
Section: Refugee Women's Attitudes Toward Ipdvmentioning
confidence: 99%
See 3 more Smart Citations